Influence of short-range correlations on ⁴He(e,e')X reaction cross section - Kuplennikov, E.L. (Вопросы атомной науки и техники, 2000)
Inelastic electron scattering on 4He nucleus is considered in the energy and momentum transfer region related with the quasifree and pion electroproduction peaks. Comparisons are shown between the data and models based on a quasifree reaction mechanism. The dynamic short-range correlation contribution is found to be significant in this kinematical region.